2013
DOI: 10.1111/jpet.12056
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Duopoly and Environment

Abstract: We show under general demand and cost conditions that in a mixed duopoly with pollution the government can implement the socially optimal outputs and abatements by a tax-subsidy scheme and keeping the public firm fully public. The scheme requires taxing outputs and subsidizing abatements at different rates, unlike a pollution tax. Our result improves on the shortcoming of a pollution tax to implement the social optimum. We also show that when the private firm is partly foreign-owned, the government will adopt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 16 publications
(21 reference statements)
3
24
0
1
Order By: Relevance
“…Furthermore, EU countries lead the development of environmental policies for the sustainability in a warming planet and have a non-negligible presence of public enterprises in energy-consuming industries such as transportation and automobile industries. More related descriptions can be found in Wang and Wang (2009), Pal and Saha (2014, 2015 and Xu, et al (2016). 3 Several researchers have recently analyzed the environmental concerns of a mixed market.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EU countries lead the development of environmental policies for the sustainability in a warming planet and have a non-negligible presence of public enterprises in energy-consuming industries such as transportation and automobile industries. More related descriptions can be found in Wang and Wang (2009), Pal and Saha (2014, 2015 and Xu, et al (2016). 3 Several researchers have recently analyzed the environmental concerns of a mixed market.…”
Section: Introductionmentioning
confidence: 99%
“…2 On the other hand, considering tax-subsidy scheme that allows for the possibility of the tax on the output and the subsidy on the abatement to be different, in a homogeneous products mixed duopoly, Pal and Saha (2014) have shown that the government can implement the socially optimal output and abatement by keeping the public firm fully public. However, it is optimal for the government to partially privatize the public firm, unless the private firm is fully owned by a domestic party.…”
Section: Barcena-ruiz Andmentioning
confidence: 99%
“…As competition intensifies, and the optimal tax is adjusted accordingly, the benefits of R&D subsidies diminish. This result complements the analysis of Pal and Saha (2014) who studied the implementation of socially optimal outputs and abatements by a tax-subsidy scheme under a mixed monopoly.…”
Section: Emissions Abatement Randd Dynamic Competition In Supply Schedusupporting
confidence: 69%